Krisis Lingkungan Berskala Internasional dalam Perspektif Fiqh Ekologi - Habibi, Muhammad; Nabilah, Febriana (Multiverse: Open Multidisciplinary Journal, 2024)
Humans, as stewards of the earth, are entrusted with the responsibility of preserving environmental balance through the use of reason and conscience, which collectively form international ecological wisdom. Environmental preservation becomes effortless and natural when rooted in everyday human practices, ensuring the sustainability of nature without the need for punitive measures or external enforcement. This paradigm is explicitly reflected in the nation's constitution, particularly in Article 33, paragraphs (3) and (4) of the 1945 Constitution, which encapsulates the principle of a "green constitution." In Islam, the divine law aims to maintain human harmony and prevent destruction. The primary sources of Islamic law—the Qur’an, hadith, and the evolving discipline of Fiqh Ecology—offer solutions to the global environmental crisis. This study employs a normative approach with a doctrinal focus and is descriptive-analytical in nature. Therefore, the research seeks to address the international environmental crisis from the perspective of Fiqh Ecology, presenting it as a framework to confront current ecological challenges.